Evaluation of Clinical and Laboratory Findings of Children Who Have Hepatitis A Virus Infection - Deveci, Ugur; Acar, Ufuk; Sali, Enes (Aves Yayincilik, Ibrahim Kara, 2021)
Objective: Hepatitis A virus (HAV) infection is a common disease in the community and can cause significant morbidity and mortality in older ages. This study to investigate and discuss the clinical and laboratory findings, treatment and prognosis of children with acute viral hepatitis A in our hospital. Material and Methods: Clinical and laboratory findings of 105 children diagnosed with acute HAV infection between January 2017 and December 2017 in Sanliurfa Training and Research Hospital, South-East Turkey, were examined. Results: 54.3% (n= 57) of the patients were males, and mean age was 6.7 +/- 3.4 years (range: 1-17 years). 65.7% of the patients were Syrian refugees, and most of the cases were admitted in winter and autumn months. The most common symptoms were jaundice (93.3%), fatigue (76.2%), fever (67.6%), anorexia (66.6%) and abdominal pain (57.1%). Serum AST, ALT, ALP, GGT, total bilirubin and direct bilirubin levels were high in all patients. Hematologic abnormalities and acute liver failure occurred in 53.4% and 3.8% of the cases, respectively. Two patients (1.9%) had gallbladder hydrops, one patient (0.9%) had reactive arthritis and one patient (0.9%) had autoimmune hepatitis. Overall mortality rate was 0.9%. Conclusion: HAV infection is still an important public health problem in our country. The disease ranges from mild clinical course to complicated cases such as acute liver failure. Improving environmental conditions along with immunization and educating the public on hygiene are very important in disease prevention.
Keywords: Hepatitis A virus; childhood; clinical; laboratory; acute liver failure